The Characteristics of the Masculinity and its Role in Women Empowerment in Pakistan - Samra Naz; Uzma Ashiq Khan; Maryam Zafar; Maryam Batool (ASIAN Journal of International Peace & Security (AJIPS), 2022)
This study aimed to explore masculine characteristics, supportive and unsupportive roles of males in women empowerment. A qualitative research with a purposive sampling technique was conducted on 20 married working and non-working female participants with age range of 18-55 years. Self-developed questionnaire in Urdu language was used for data collection. Data was gathered through in-depth semistructured interviews. After transcribing interviews, data was analyzed through thematic analysis. About twenty-four major themes emerged. For father’s role; strong support system, role model, skill & personality developer, vigilant role in socialization, supporter in pursuing education, psychological and emotional bonding, health caregiver, activity and recreation, influential personality, career aspirations. Brother role is defined as; unconditional supporter, intimate siblings about career building, positive support in academics, health caregiver, partner in crime, strong communication. Husband role was categorized as; Intimate partner about family planning matters, emotional & psychological support, participation in household work, productive and influential in career development, caring & nurturing attitude about children, equal decision-maker, benevolent sexism, hostile sexism. It was found that working and non-working women have more support from their fathers in every aspect of their life. Brothers have not been playing significant role in non-working female lives. While husbands are more supportive for female who were career oriented as compared to housewives.